Antibacterial activity of polypyrrole-based nanocomposites: a mini-review - Silva Júnior,Fernando Antonio Gomes da (2020)
Abstract The development of polypyrrole-based nanocomposites as alternative antibacterial agents represents a promising strategy to be applied against the prevailing multi-resistant bacteria. Herein, it is reported the most recent development of antibacterial materials based on the combination of polypyrrole and different fillers (metal nanoparticles, carbon nanotubes, and polysaccharides) and strategies to improve their action (such as light and electrical stimulus). The synergistic interaction of electrostatic forces provided by charged polypyrrole combined with the permeation of nanoparticles through the cell wall favors the leakage of cytoplasmic components and reinforces the antibacterial activity of the resulting material, observed in all-organic composites of polypyrrole and chitosan that reached superior performance against Escherichia coli (108 CFU) or metal-polymer composites (polypyrrole-palladium) with an outstanding performance against different types of bacteria. The development of binary and ternary composites is explored to potentialize the antibacterial synergy of components.